ECO PRINT BUSINESS ACCOUNTING SIMULATION IN ENTREPRENEURSHIP TRAINING FOR STUDENTS OF ASWAJA ISLAMIC BOARDING SCHOOL - Popy Novita Pasaribu; Indupurnahayu; Budi Susetyo; Dwi Maulina; Dzahwana Adnan; Abdullah Azzam Hamasah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study aims to assess the impact of Eco print-based business accounting simulations on improving financial literacy and entrepreneurial mindset among students at Pondok Pesantren Al-Umm ASWAJA. In the modern era, Islamic boarding schools are encouraged to integrate skills and entrepreneurship education into their curricula to prepare students to face challenges, particularly in the creative and digital economies. The study consists of two main stages: observation and interviews, followed by the training session. The first stage involves identifying existing issues through observation and preliminary interviews with the pesantren leadership, which is essential for designing a targeted training program. The second stage focuses on the implementation of the Eco print and basic business accounting training. The training includes theory presentations, practical exercises, and a simulation of basic accounting concepts such as cost calculations and financial reporting. The results of the pretest and posttest evaluations revealed significant improvements in the participants’ knowledge of Eco print techniques, basic accounting, and entrepreneurship. The findings suggest that integrating Eco print techniques with business accounting simulations positively influences the participants’ financial literacy, entrepreneurial mindset, and awareness of sustainable business opportunities. This training not only enhances practical skills but also fosters an entrepreneurial spirit, which is crucial for students in the modern business world. The study concludes that a hands-on approach in learning, particularly one that combines creativity with financial literacy, is an effective method for enhancing the entrepreneurial potential of Islamic boarding school students. The outcomes indicate a promising approach to integrating traditional Islamic education with modern entrepreneurial skills, providing a solid foundation for students to succeed in the evolving economy.